2011
DOI: 10.1016/j.cell.2011.06.051
|View full text |Cite
|
Sign up to set email alerts
|

The Human Mitochondrial Transcriptome

Abstract: Summary The human mitochondrial genome comprises a distinct genetic system transcribed as precursor polycistronic transcripts that are subsequently cleaved to generate individual mRNAs, tRNAs and rRNAs. Here we provide a comprehensive analysis of the human mitochondrial transcriptome across multiple cell lines and tissues. Using directional deep sequencing and parallel analysis of RNA ends, we demonstrate wide variation in mitochondrial transcript abundance and precisely resolve transcript processing and matur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

43
832
6
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 780 publications
(884 citation statements)
references
References 63 publications
43
832
6
3
Order By: Relevance
“…(3) The two RNA-seq data sets 8,9 used in this study were Expression variability of mitochondrial DNA-encoded genes G Wang et al derived from poly(A)-enriched RNA pools, and were not generated using strand-specific RNA-seq. These might influence the estimation of the levels of mtDNA gene expression because of the different polyadenylation statuses of mtDNA genes 13,60,61 and the possible cross-mapping between L-and H-strand-derived mitochondrial transcripts. 60 Nevertheless, because these technical limitations systematically influenced all samples in the same manner on the same order of magnitude, our main results in connection with the between-individual expression variability should not be affected.…”
Section: Discussionmentioning
confidence: 99%
“…(3) The two RNA-seq data sets 8,9 used in this study were Expression variability of mitochondrial DNA-encoded genes G Wang et al derived from poly(A)-enriched RNA pools, and were not generated using strand-specific RNA-seq. These might influence the estimation of the levels of mtDNA gene expression because of the different polyadenylation statuses of mtDNA genes 13,60,61 and the possible cross-mapping between L-and H-strand-derived mitochondrial transcripts. 60 Nevertheless, because these technical limitations systematically influenced all samples in the same manner on the same order of magnitude, our main results in connection with the between-individual expression variability should not be affected.…”
Section: Discussionmentioning
confidence: 99%
“…First, two recent, independent studies have shown the presence of the RNA subunit of both P and MRP RNases in the matrix of human mitochondria (97,99). Although the corresponding protein subunits have not been found in this organelle, from the protein composition already described, it can be inferred that their function could be performed by a different set of proteins.…”
Section: Exceptions To the Rule: Uncommon Sources For Rnase P/mrp Funmentioning
confidence: 98%
“…The 16,569‐bp human mtDNA contains 13 genes that codify proteins involved in mitochondrial oxidative phosphorylation (OXPHOS), as well as 2 rRNA and 22 tRNA genes that are necessary for protein synthesis within mitochondria (Mercer et al ., 2011). Mitochondria are one of the most important players to understand the aging process at the cellular level as they are both the main source and target of oxidative damage (Gomez‐Cabrera et al ., 2012).…”
Section: Mitochondrial Haplogroups and Elmentioning
confidence: 99%